Lung cancer in Japanese chromate workers. Issue 3 (June 1978) - Ohsaki, Y; Abe, S; Kimura, K; Tsuneta, Y; Mikami, H; Murao, M
Abstract : We have treated ten patients with lung cancer among workers in a chromate factory between 1972 and 1976. Four further cases were also found through death certificates and medical records. Most were smokers and all were men. The average duration of exposure to chromate was 24 years (range 10 to 36). The cell type in our ten patients was squamous in seven and small anaplastic type in three. The primary sites were all in large bronchi. The incidence (person per year) calculated from the number of employees, duration of factory activity, number of cancer patients, and shortest duration of labour period among the patients was 657.9 per 100, 000 compared to 13.3 per 100, 000 in Japan as a whole.